In-situ X-ray photoelectron spectroscopy analysis of the initial growth of CdS thin films by chemical bath deposition - Garza-Hernández, R. (2019)
Cadmium sulfide is the main choice among n-type semiconductors for several solar cell technologies due to its excellent optical, structural and electronic characteristics. Even when it has been widely studied, there are still unsolved aspects related with the understanding of nucleation and growth mechanisms. For that, the initial growth stages of CdS deposited by chemical bath deposition (CBD) were carefully studied by in-situ X-ray photoelectron spectroscopy (XPS) by connecting a glove box with the CBD setup to the XPS introduction chamber. The CdS thin films were synthesized by CBD method onto glass substrates using CdCl2 as the cadmium precursor, sodium citrate as the complexing agent and thiourea as the sulfur source. XPS analysis revealed the presence of Cd(OH)2 and Cd-Citrate species, which facilitates nucleation to later promote the formation of CdS. During the deposition time (0–10 min) the pH changes from 12.1 to 10.8. Considering this, the following combination of mechanisms during the deposition: the hydroxide (above pH 11) and complex-decomposition (below pH 11) was proposed by using a distribution species diagram. The resulting films are close to the ideal stoichiometric CdS after 10 min of deposition. Furthermore, the film thicknesses determined by XPS ultra-thin film analysis, were about 2.37 and 13.7 nm, for 6 and 10 min, respectively, in good agreement with ellipsometry measurements.